AN ASSESMENT OF THE INFLUENCE OF QUESTIONING LEARNING STRATEGY ON STUDENTS’ CREATIVITY DEVELOPMENT IN SECONDARY SCHOOLS IN MUKAA SUB –COUNTY MAKUENI COUNTY, KENYA. - Marete, Bundi; KITUU, SHEDRACK; Macharia, Dr. Susan; Njoroge, Dr. Benson (IJRDO- Journal of Educational Research, 2018)
Creativity, a 21st century skill is vital for the success of learners. Studies have shown that, the level of creativity in secondary school students has reduced. Some of the evidences of the reduced level of creativity is the students’ low ability to come up with original ideas in Science fair projects, music and drama as well as coming up with entrepreneurial ideas that they can use to earn a living after form IV. The objectives of the study were to examine the extent to which questioning learning strategy influences students in making them: think more, increasing their inquisitivity, acquiring and retaining knowledge as well as reading more to get answers and understand better. The study was informed by discovery learning theory of Brunner and the creativity development theory by Wallas. The study employed mixed methods research methodology. The descriptive survey and phenomenology designs were employed. From the target population of 39 secondary schools, the researcher sampled 12 schools which represented 30.8% of the target population using stratified sampling. From the 12 schools, the researcher solicited data from their 3 science teachers per school and 25 form IV students per school. The study revealed that, questioning learning strategy influences students’ creativity development significantly by making them: think more, increasing their inquisitiveness (ability to question), acquiring and retaining knowledge, making them read more to get answers and understand better. Analysis of data showed that there is a strong positive relationship between questioning learning strategy and students’ creativity development.